2015
DOI: 10.1002/adfm.201502929
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Free Synthesis of Aluminum‐Doped Zinc Oxide Nanocrystals and their Use as Optical Spacers in Color‐Tuned Highly Efficient Organic Solar Cells

Abstract: Abstract:The color of polymer solar cells using an opaque electrode is given by the reflected light, which depends on the composition and thickness of each layer of the device. Metal oxide based optical spacers were intensively studied in polymer solar cells aiming to optimize the light absorption. However, the low conductivity of materials such as ZnO and TiO 2 limits the -----

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 47 publications
3
59
0
1
Order By: Relevance
“…The work functioni s4 .08 eV with conduction band energyo f3 .79 eV and ionization potential of 7.87 eV as determined in Ref. [14].T hese values suggest that AZO is ap romising candidate to be used as an electronselectivel ayer in organic photoelectrochemicald evices anda n illustrative energy diagram of the full device is showeda sF igure 2a.A verage mobility values of m = 210 À5 cm 2 Vs À1 were extracted from field-effect transistors measurements (see Figures SI2 andS I3 for details). Although this is not an extremely high value, it is adequate to be used in devicesw ith af ew tens of nanometers.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…The work functioni s4 .08 eV with conduction band energyo f3 .79 eV and ionization potential of 7.87 eV as determined in Ref. [14].T hese values suggest that AZO is ap romising candidate to be used as an electronselectivel ayer in organic photoelectrochemicald evices anda n illustrative energy diagram of the full device is showeda sF igure 2a.A verage mobility values of m = 210 À5 cm 2 Vs À1 were extracted from field-effect transistors measurements (see Figures SI2 andS I3 for details). Although this is not an extremely high value, it is adequate to be used in devicesw ith af ew tens of nanometers.…”
Section: Introductionmentioning
confidence: 53%
“…The work function is 4.08 eV with conduction band energy of 3.79 eV and ionization potential of 7.87 eV as determined in Ref. . These values suggest that AZO is a promising candidate to be used as an electron‐selective layer in organic photoelectrochemical devices and an illustrative energy diagram of the full device is showed as Figure a.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…By modulating the thickness of transparent ILs, it is possible to enhance photocurrent via the optical spacer effect . Optical spacer ILs can improve the spatial distribution of light inside the solar cell and thus enhance photon absorption within the photoactive layer . Park et al demonstrated a device based on an active BHJ composite of poly(( N ‐9'‐heptadecanyl‐2,7‐carbazole)‐ alt ‐(5,5‐(4',7'‐di‐2‐thienyl‐2',1',3'‐benzothiadiazole))) ( PCDTBT )/ PC 71 BM , which had an internal quantum efficiency close to 100% upon the addition of a TiO x optical spacer layer and a PCE of 6% .…”
Section: Role Of the Interfacial Layermentioning
confidence: 99%
“…An efficient ETL with thickness over 600 nm can be prepared at low temperature (140 °C) without significantly drawing down PCE. In addition, Gaceur et al also report Al:ZnO nanocrystal as efficient ETL without high‐temperature annealing 70a. With the Al doping, the nanocrystals not only exhibit improved conductivity but also show good film formation for a smooth thin film, which together contribute to a higher PCE of 7.56% compared to that of undoped ZnO of 5.86% in PTB7:PCBM based organic SCs.…”
Section: Recent Progress Of Solution‐processed Ternary Oxide–based Ctlsmentioning
confidence: 99%